Gendered impacts of the war in Ukraine: identifying potential, presumed or actual women victims of trafficking at the Italian borders - Cimino, Francesca; Degani, Paola (Frontiers in Human Dynamics, 2023)
According to the United Nations High Commissioner for Refugee (UNHCR) data, approximately 8 million people, mostly women and children, entered and registered in Europe since the beginning of the war on the 24th of February, 2022 (UNHCR, 2023). It is well known that human trafficking tends to increase during conflicts and humanitarian crises due to the spread of impunity, destruction of institutions, and breakdown of law. The EU and many international organizations have warned those fleeing Ukraine about the high risk of trafficking and adopted policies to prevent and detect trafficking. The EU anti-trafficking coordinator along with other EU agencies have developed the Common Anti-Trafficking Plan to specifically address this risk and support the potential victims fleeing the war in Ukraine (EU Solidarity Platform, 2022) meeting one of the goals set in the 10 Point Action Plan issued by the European Council in March (European Council, 2022) to better coordinate EU actions for people leaving Ukraine. Among other goals, the 10 Point Action Plan aims to improve early identification of the victims of human trafficking as provided by the 2021–2025 Strategy on Combatting Trafficking (European Commission, 2021) and the 2011 Anti-trafficking Directive.This paper investigates the actions which the Italian government has put in place to detect and prevent the trafficking of women among the Ukrainians fleeing the war, with a focus on the identification process. More specifically we explored the perceptions of front-line workers and street-level bureaucrats at the Slovenian and Austrian borders, where Ukrainians cross to enter Italy. Through interviews we collected data to shed light on the identification procedures adopted. The need to learn more about the current war in Ukraine corroborates this study. The proposed qualitative analysis has identified three main findings: 1) conflicts create increased opportunities for trafficking that in the case of Ukraine are greater due to the scale of those fleeing; 2) temporary Italian residence permit reveals some criticalities that could lead to greater vulnerability; 3) gaps in the identification process can increase the risks of trafficking, especially in the absence of longer-term assistance programs.